Key characteristics in designing massive open online courses (MOOCs) for user acceptance: an application of the extended technology acceptance model - Tao, Da; Fu, Pei; Wang, Yunhui; Zhang, Tingru; Qu, Xingda (Interactive learning environments, 2022)
In spite of the proliferation of Massive Open Online Courses (MOOCs) in higher education, factors influencing user acceptance of MOOCs are not well understood. This study is intended to investigate key characteristics of user acceptance from interface design (i.e. usability), content quality (i.e. perceived quality), and emotional arousal (i.e. perceived enjoyment) of MOOCs within the framework of Technology Acceptance Model (TAM). Six hundred and sixty-eight college students were invited to complete a self-reported questionnaire measuring TAM constructs and three hypothesized variables drawn from MOOC characteristics. The results from path analysis showed that all path coefficients were statistically significant. Perceived ease of use, perceived usefulness and perceived enjoyment significantly affected students' behavioral intention to use MOOCs, while both perceived usefulness and behavioral intention yielded a significant influence on perceived effective use of MOOCs. Usability and perceived quality had a strong indirect impact on behavioral intention and perceived effective use through the mediators of perceived ease of use, perceived usefulness and perceived enjoyment. This study demonstrated that the extended TAM with MOOC characteristics provides an effective means to understand students' acceptance of MOOCs.